THE ROLE OF THE NEWSPAPER “ERKIN TOO” IN THE FORMATION OF STATEHOOD IN 1924–1927 (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines events related to the publication of the newspaper Erkin Too in 1924, the formation of the Kyrgyz Autonomous Region, its transformation into an autonomous republic in 1926, the activities of the intelligentsia of that time, and the historical developments up to 1927 during the process of state formation as reflected in the newspaper’s pages. It also mentions how some individuals who rejected the new era attacked correspondents, forcing them to write under pseudonyms. The article highlights the arrival of Intergelpo, the pursuit of education, and issues concerning women’s rights.
Keywords: October Revolution, autonomous republic, Intergelpo, agitation and propaganda, workshop, women’s rights, cooperative.